Revised and extended benchmark results for Rayleigh scattering of sunlight in spherical atmospheres. (October 2020) - Korkin, Sergey; Yang, Eun-Su; Spurr, Robert; Emde, Claudia; Krotkov, Nickolay; Vasilkov, Alexander; Haffner, David; Mok, Jungbin; Lyapustin, Alexei
Highlights: Accurate numerical results to test spherical RT codes are hard to find in literature. We reproduced, with better accuracy, the results by Adams and Kattawar [1] . We used RT codes MYSTIC (Monte Carlo, true spherical atmosphere) and VLIDORT (discrete ordinates, corrected for the effect of spherical atmosphere). We extended the results by A&K for relative azimuth other than 0–180° (principal plane). Results of our simulation are reported in numerical format. Abstract: While most of traditional Earth-atmosphere satellite remote sensing relies on radiative transfer (RT) in the plane parallel geometry, effects of sphericity are important at high sun and view zenith angles. Broad understanding of these effects is limited and, contrary to the plane-parallel case, finding accurate numerical results to test spherical RT codes is not easy. This paper aims to partially fill in this gap. Using the full-spherical RT code MYSTIC (Monte Carlo), and the plane-parallel RT code VLIDORT (discrete ordinates) corrected for atmospheric sphericity in the single and multiple scattering, we reproduced with better accuracy and extended the benchmark results by Adams & Kattawar [1] .